Feasibility štúdia projektu výroby biomasy - Karaba, Ján; Fotr, Jiří, 1938-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2008)
The objective of this thesis is to assess the overall feasibility of a biomass production project in the current business environment in Slovakia. The project is analyzed primarily in terms of market conditions, technical and technological details and economic feasibility. An important part of the study is also the risk analysis including various scenarios and an assessment of the influence of risk factors. The thesis concludes that the project is essentially feasible and has a potential of being successful although it bears a certain level of riskiness which has to be considered and managed.
Vedoucí práce: Jiří Fotr
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2008
Rok obhajoby 2008
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses